(untitled) (Ágora de Heterodoxias, 2019)
The writer Domingo Miliani warns about the recurrence of the thread as a symbol of continuity after the finite (of the necessity of the imperishable, of life in spite of death), in the poetry of Andrés Eloy Blanco, famous popular poet of Venezuela, who was also a transcendent figure in national policy in the first half of the twentieth century. Trying to bring new readings to Miliani’s findings on the woven thread in Blanco’s poetics, and given what seems to be an invitation made at that time by the master Luis Beltrán Prieto Figueroa - to continue stirring into the constant of this metaphor of the thread in the work of Andrés Eloy Blanco there is an exercise is interpreting this rhetorical resource on yarn and the weaving as elements that aligned and mended a moral plot in the poet´s times, both in journalistic prose and essays including his speeches as a parliamentarian, and in the times of his exile in Mexico, between 1948 and 1955, the year of his death, which ocurred in Cuernavaca. In essence, the poet’s thinking in the texts treated has a moral tendency of a deontological nature.